Pengaruh Motivasi Kerja Dan Lingkungan Kerja Pada Era New Normal Terhadap Kinerja Karyawan PT JasaRaharja Putera (Persero) Cabang Palembang - Desti Andelia; Wiwin Agustian (Jurnal Pendidikan dan Konseling (JPDK), 2022)
The formulation of the problem in this study is whether there is an effect of work motivation and work environment on employee performance at PT JasaRaharja Putera (Persero) Palembang branch. This study aims to determine the effect of work motivation and work environment on the performance of employees of PT JasaRaharja Putera (Persero) Palembang branch. The location of this research is addressed at JL. Kapten A. Riva'i No. 18, Sungai Pangeran. district. Ilir Timur 1. Palembang, South Sumatra. The population used in the study were 40 employees who worked at PT JasaRaharja Putera (Persero) Palembang branch. The data collection technique in this study was a questionnaire. The hypothesis test used in this study is the t test and f test. The results of this study indicate that work motivation and work environment affect employee performance at PT JasaRaharja Putera (Persero) Palembang branch.